Implementasi Teori Belajar Behavioristik dalam Transformasi Perilaku Religius Peserta Didik pada Pembelajaran PAI - Widia Yelsa; Fatmawati; Ismail Syakban; Julhadi (STKIP Subang, 2026)
This study aims to analyze the mechanisms of behaviorist learning theory and its strategic implementation in transforming the religious behavior of learners within Islamic Education (PAI) subjects. Amid the challenges of moral degradation and the complexities of the digital era, the effectiveness of PAI is often hindered by the dominance of cognitive knowledge transfer, which overlooks the internalization of values (transfer of values). Utilizing a systematic literature review method on modern educational psychology discourse and Islamic educational thought, this study dissects the theoretical contributions of Ivan Pavlov, Edward Thorndike, and B.F. Skinner within the context of shaping akhlakul karimah (noble character). The research findings indicate that applying principles of classical conditioning, connectionism, and operant conditioning through shaping techniques, positive reinforcement, and multimodal stimulus management can optimize PAI learning outcomes by up to 40%. The integration of behaviorist concepts with traditional Islamic methods—such as riyadhoh (spiritual training), targhib (promise of reward), and tarhib (threat of sanction)—creates an applicable framework for forming spontaneous and enduring patterns of religious behavior. This study concludes that the transformation of religious behavior requires a controlled instructional environment engineering to ensure observable and concretely measurable behavioral changes